Fabrication of wavy micromixer using soft lithography technique. (2020) - Mondal, Bappa; Pati, Sukumar; Patowari, Promod Kumar
Abstract: Microfluidic devices are enormously used in different engineering applications such as biological, chemical, electronics, mechanical, etc. Manufacturing of microfluidic devices becomes one of the emerging areas of research in the current times. Manufacturing of microfluidic devices is a challenging issue via general fabrication technologies. Several types of materials and methods are in use for fabricating microfluidic devices for different kinds of uses. Micromixer is an essential component to integrate any microfluidic device. In this paper, a fast process for the fabricating of micromixer with poly-di-methyl-siloxane (PDMS) is presented and elaborated. Two types of wavy micromixers, namely raccoon, and serpentine are fabricated. The complete fabrication process of the micromixer has been conducted with major two steps, namely, mold preparation, and fabrication. Initially, the mold of the micromixer of raccoon, and serpentine type with proper dimensions is produced using CO2 assisted laser machining on poly-methyl-meth-acrylate (PMMA), and then using these molds, micromixer of PDMS is prepared by soft lithography technique. Micromixer with accurate and precious dimensions as per the required design can be fabricated using the proposed process for different purposes. This article may be helpful for the researchers to get the proper knowledge related to the fabrication of wavy micromixer in a fast and cost-effective way.